APIcator / Alya Nurizzati Muhamad Basir ...[et al.] - Muhamad Basir, Alya Nurizzati; Zaidi, Nur Fizliyana Ezzati; Radzi, Nur Diyana; Khairol Anuar, Hanis Sakinah (2019)
APIcator usally use when the air turns nearly bad or really bad such as haze. It helps to collect the air quality from the place that are out from the government or the DOE coverage. The DOE only cover 65 areas in Malaysia (APIMS, n.d.) and mostly the stations are located at the main city. Thus, there are some places not accurately covered by the government .With the APIcator, the user will get more accurate reading of API of the current place that the user be. Its detect the air surrounding and update the status of API real timely through an application that connected with the device. This is not only provide the details of API reading in particular places but also improve the accuracy of the government data. This is because the data from APIcator will integrate with government data and produce highly accurate API reading. Before data is integrated, it's store in the cloud storage and the government or Department of Environment(DOE) can also access the data collected. Owning APIcator helped in getting continuous data and prevent from received inaccurate reading. This is because the device have bluetooth so if the connection is loss, the device doesn't have to solely depend on the internet for the data to be shared to the user. This is due to the technical issue that had occurred before this, On September 17 at 1pm and 6pm.